A Case Report of Giant Cell Tumor of Proximal Fibula in Children - Adhikari, Sushil; Sigdel, Arun; Sah, Rajesh Kumar; Devkota, Luna (Nepalese Journal of Cancer, 2020)
Giant cell tumour (GCT) is histopathologically benign tumor of long bone particularly in distal femur and the proximal tibia. It commonly occurs in adults of age 20-40 years but rare in children. GCT is considered to be locally aggressive tumor and tendency of recurrence is higher even after surgery. The clinical features are nonspecific, the principle symptoms are pain, swelling and limiting adjacent joint movements. Diagnosis is based on the radiographic appearance and histopathological findings .In our case X-ray showed ill defined lytic lesion on proximal fibula with cortical thinning and MRI finding revealed expansile lyticlesion in meta-epiphysis of right fibula 16×16×28mm adjacent to growth plate with fluid level. The sclerotic rim appears hypo intense on T1 & hyper intense on T2. Core needle biopsy showed giant cell tumor on proximal fibula. Considering the risk of recurrence wide local excision was done. Management of GCT of proximal fibula in young patient is critical for preventing recurrence and enhancing functional outcomes by saving adjacent anatomical structure. No evidence of local recurrence and metastasis was found in 24 months of follow up.